the EVALUATION OF ANTI-DIABETIC ACTIVITY OF METHANOLIC EXTRACT FROM THE FRUIT PEEL OF ATALANTIA MONOPHYLLA (LINN.) IN ALLOXAN INDUCED DIABETIC MICE - GODSE KIRTI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Atlantia monophylla is an indigenous medicinal plant, with a folk reputation as hypoglycemic agent throughout India. Considerable research has shown that plants rich in flavonoids content with anti-oxidant potential are known to be bioactive for the management of diabetes mellitus (DM). In the present investigation, hypoglycemic activity of aqueous fruit peel extract of A. monophylla was evaluated using alloxan-induced hyperglycemic mice. Methods: Aqueous extract of the fruit peel of A. monophylla (AEAM) was subjected to preliminary phytochemical screening and acute oral toxicity study as per Organization for Economic Cooperation and Development guidelines 425. AEAM was evaluated for hypoglycemic activity, Alloxan induced DM in mice, oral glucose tolerance test in fasted mice. In vitro α- amylase inhibitory in albino mice method was employed for evaluation of hypoglycemic activity. Results: All of the mice in each group had their blood glucose levels measured both before and after the treatments on fasting animals. The extract was given at doses of 200 mg/kg and 400 mg/kg body weight, or 100 mg/kg body weight of the conventional antidiabetic medication Metformin. A glucometer was used to measure the blood glucose level. After 1 h, 2 h, and 4 h, the extract-treated diabetic mice had a substantial (p≤0.05) drop in blood glucose levels. The hypoglycemic action was similar to that of the medication Metformin used as a benchmark. Conclusion: The results of this study indicate that AEAM has strong hypoglycemic properties. One such method might include the activation of insulin receptors and subsequent release of insulin once β cells are stimulated. The hypoglycemic effect of the plant could be achieved through increasing insulin release from the pancreas.